2016
DOI: 10.4269/ajtmh.15-0733
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Toxocariasis: A Neglected But High-Prevalence Disease in Brazil

Abstract: Abstract. Toxocariasis is an anthropozoonosis that occurs in all parts of the world. In particular, this disease can often be found in developing countries and in regions, where basic sanitation conditions are poor. However, industrialized countries have reported seroprevalence rates as high as 14.2% in humans. The definitive hosts of the disease are dogs and cats, whereas humans are a paratenic host. To determine the burden of toxocariasis in Brazil, we followed the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…These findings were similar to those reported in earlier bibliometric studies [55][56][57], which found that the economic growth of a country affected the quantity of research published by its researchers. Developing countries, such as Brazil, Poland, Argentina and India, showed a noticeable increase in published papers on toxocariasis research in recent years, which may have been coincident with a high prevalence of toxocariasis in these countries [31,[58][59][60]. The United States and the United Kingdom had the highest number of collaborations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were similar to those reported in earlier bibliometric studies [55][56][57], which found that the economic growth of a country affected the quantity of research published by its researchers. Developing countries, such as Brazil, Poland, Argentina and India, showed a noticeable increase in published papers on toxocariasis research in recent years, which may have been coincident with a high prevalence of toxocariasis in these countries [31,[58][59][60]. The United States and the United Kingdom had the highest number of collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…The terms "toxocar*", "nematode ophthalmitis", "visceral larva migrans", "ocular larva migrans", "Nematode endophthalmitis", "dog roundworm" and "cat roundworm" were used as keywords to search titles. These keywords were based on previous review articles [6,[29][30][31]. The asterisk (*) was applied as a wildcard and enabled the search for variations of key terms.…”
Section: Methodsmentioning
confidence: 99%
“…If these infective eggs (containing a L2 larva) are ingested by human, in the duodenum, the larva will hatch and find its route to the liver via the portal circulation, then from vascular channels to the lung systemic circulation. Eventually, larva will settle in various organs and tissues, including eye, brain, lungs, liver, and muscles, resulting in two major clinical syndromes of toxocariasis, visceral larva migrans (VLM) and ocular larva migrans (OLM) (Bae et al 2016;Despommier 2003;Fialho et al 2016;Fisher 2003). Other recognized clinical manifestations include neurological toxocarisis and occult toxocariasis (Mazur-Melewska et al 2015;Pawlowski 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the public health and clinical significance of human toxocariasis, particularly in tropical and subtropical regions of the world and in underprivileged communities in temperate climatic zones (Fialho and Corrêa, 2016;Hotez and Wilkins, 2009;Lee et al, 2014;Macpherson, 2013;Overgaauw, 1997;Rubinsky-Elefant, 2010), considerable knowledge gaps in the epidemiology of this disease exist (Çelik et al, 2013;Cooper, 2008;Holland, 2015;Hotez and Wilkins, 2009;Le et al, 2016;Poulsen et al, 2015;Smith et al, 2009). Recent studies indicate that toxocariasis is neglected, and it is not a notifiable disease (Fu et al, 2014;Hayashi et al, 2005;Won et al, 2008).…”
Section: Introductionmentioning
confidence: 99%